Report on the assessment of CHED's HRD needs - Legaspi, Perla E. ([Commission on Higher Education], 2001)
"An HRD consultant from the National College of Public Administration and Governance of the University of the Philippines was therefore requested to provide the needed technical assistance on the following areas: 1. Review and assessment of the HRD needs of the CHED. 2. Formulation of an HRD plan for the Commission."--P. 1.